Case Report: PD-L1-negative advanced bladder cancer effectively treated with anlotinib and tislelizumab: A report of two cases - Li, Teng; Hu, Wuyun; Jin, Lan; Yin, Xianghua; Kang, Dongxu; Piao, Longzhen (Frontiers in Oncology, 2023)
Background: Second-line treatment for metastatic or locally advanced urothelial cancer (UC) is limited. Immunotherapy is approved as a second-line treatment for metastatic UC. Its use as a first-line agent is limited to patients who are ineligible for cisplatin-based treatments. The fibroblast growth factor receptor (FGFR) inhibitor, erdafitinib, can be applied as a third-line approach after the failure of these prior treatments in eligible patients. Therefore, it is especially important to combine limited drugs for second-line treatment of advanced or metastatic UC. Anlotinib is a multiple tyrosine kinase inhibitor agent with both anti-angiogenic and FGFR inhibitory effects. For two patients with advanced and metastatic UC, we coupled anlotinib and tislelizumab therapy, even though there is no indication for its use. Case presentation: We describe two patients with PD-L1-negative advanced bladder cancer, one with FGFR3 mutation and the other FGFR3 wild-type. Both patients had progressed after first line chemotherapy with gemcitabine and cisplatin. We selected anlotinib in combination with tislelizumab, a PD-1 immune checkpoint inhibitor, for second-line treatment. Responses were evaluated as partial remission in both cases, who achieved up to 12 months of progression-free survival with no significant adverse events. Conclusion: Two patients with PD-L1-negative UC, underwent second-line therapy using tislelizumab in combination with anlotinib, and the efficacy was better than that of tislelizumab alone. These results suggest that anlotinib may act synergistically with tislelizumab in treatment of UC.